Keterkaitan Personal Growth Initiative dan Harapan dengan Adaptabilitas Karir pada Mahasiswa Vokasi - Pertiwi, Hartawati Indah; Pramono, Ridwan Budi (Jurnal Psikologi Perseptual, 2024)
This study aims determine the relationship between personal growth initiative and hope with career adaptability in vocational students in Indonesia. The participants in this study are vocational students in Indonesia. The data collection technique used in this study is a simple random sampling technique with data collection instruments including career adaptability scales, personal growth initiative scales, and hope scales The result of this study showed a correlation coefficient of 0.769 with a p of 0.000 (p0.01) which showed a very significant relationship between personal growth initiative and hope with career adaptability in vocational students, with an effective contribution of 59.1%, thus the major hypothesis in this study was accepted. The result of the correlation coefficient between personal growth initiative and career adaptability were obtained 0.734 with a p of 0.000 (p0.01), which shows that there is a very significant positive relationship between personal growth initiative and career adaptability, thus the first minor hypothesis proposed in this study accepted. While the correlation coefficient between hope and career adaptability shows an r value of 0.581 with a p of 0.000 (p0.01), this shows that there is a very significant positive relationship between hope and career adaptability, thus the second minor hypothesis in this study accepted.Penelitian ini bertujuan untuk mengetahui hubungan personal growth initiative dan harapan dengan adaptabilitas karir pada mahasiswa vokasi di Indonesia. Partisipan dalam penelitian ini merupakan mahasiswa vokasi di Indonesia. Teknik pengambilan data yang digunakan dalam penelitian ini adalah teknik simple random sampling dengan instrumen pengumpulan data meliputi skala adaptabilitas karir, personal growth initiative, dan juga harapan. Hasil penelitian ini menunjukkan koefisien korelasi sebesar 0,769 dengan p sebesar 0,000 (p 0,01) yang menunjukkan adanya hubungan yang sangat signifikan antara personal growth initaitive dan harapan dengan adaptabilitas karir pada mahasiswa vokasi, dengan sumbangan efektif 59,1%, dengan demikian hipotesis mayor dalam penelitian ini diterima. Hasil koefisien korelasi antara personal growth initiative dengan adaptabilitas karir diperoleh sebesar 0,734 dengan p sebesar 0,000 (p 0,01), hal ini menunjukkan adanya hubungan positif yang sangat signifikan antara personal growth initiative dengan adaptabilitas karir, dengan demikian hipotesis minor pertama yang diajukan dalam penelitian ini diterima. Sementara itu koefisien korelasi antara harapan dengan adaptabilitas karir menunjukkan nilai r sebesar 0,581 dengan p sebesar 0,000 (p 0,01), hal ini menunjukkan adanya hubungan positif yang sangat signifikan antara harapan dengan adaptabilitas karir, dengan demikian hipotesis minor kedua dalam penelitian ini diterima.